Amiodarone hydrochloride: enhancement of solubility and dissolution rate by solid dispersion technique - Alexandre Machado Rubim; Jaqueline Bandeira Rubenick; Eduarda Gregolin; Luciane Varini Laporta; Rosimar Leitenberg; Clarice Madalena Bueno Rolim (Universidade de São Paulo, 2015)
abstract Amiodarone HCl is an antiarrhythmic agent, which has low aqueous solubility and presents absorption problems. This study aimed to develop inclusion complexes containing hydrophilic carriers PEG 1500, 4000 and 6000 by fusion and kneading methods in order to evaluate the increase in solubility and dissolution rate of amiodarone HCl. The solid dispersion and physical mixtures were characterized by X-ray diffraction, FT-IR spectra, water solubility and dissolution profiles. Both methods and carriers increased the solubility of drug, however PEG 6000 enhanced the drug solubility in solid dispersion better than other carriers. Different media were evaluated for the solubility study, including distilled water, acid buffer pH 1.2, acetate buffer pH 4.5 and phosphate buffer pH 6.8 at 37 ºC. Based on the evaluation of the results obtained in the study phase solubility carriers PEG 4000 and PEG 6000 were selected for the preparation of the physical mixture and solid dispersion. All formulations were prepared at drug-carrier ratios of 1:1 to 1:10(w/w). The results of in vitro release studies indicated that the solid dispersion technique by fusion method in proportion of 1:10 (w/w) increased significantly the dissolution rate of the drug. X-ray diffraction studies showed reduced drug crystallinity in the solid dispersions. FT-IR demonstrated interactions between the drug and polymers.